Structural design and vibration characteristics of a contra-rotating drilling tool based on planetary gear trains - Qian, Li; Xuyong, Liu; Huaiwei, Liu; Zhigang, Zhu; Hehong, Deng; Guangjun, Li; Haina, Zhou; Xuming, Feng; Yuefei, Zeng (Frontiers in Mechanical Engineering, 2026)
IntroductionTo reduce severe drill string vibration and improve drilling efficiency in deep drilling, which are often accompanied by significant energy loss.MethodThe contra- rotation of the inner and outer drill bits was facilitated by planetary gear transmission, and the anti-torque fluctuation was reduced by the torque balance principle, thereby suppressing vibration. In this paper, the design of the gear, bearing, and seal structure of the contra-rotating drilling tool was completed; single rotation and contra-rotating drilling tools were prepared alongside artificial rock samples; a drilling test rig was constructed; and vibration signals of the drilling tools were collected at different rotation speeds.ResultTime-domain and frequency-domain analyses revealed that the vibration acceleration amplitude of the contra-rotating drilling tool in the X, Y, and Z directions is significantly lower than that of the single rotation drilling tool. Furthermore, with increasing rotation speed, the vibration amplitude of the contra-rotating drilling tool remains stable or even decreases, whereas the vibration of the single rotation drilling tool increases significantly.DiscussionA mechanistic analysis revealed that the contra-rotating drill bit requires less driving force to break rock, produces more shear failure zones, breaks rock more easily, and generates less vibration. This study provides an effective active control method for reducing drilling vibration and has good prospects for application in the field of engineering.